KAJIAN SLANG AUSTRALIA: PROSES MORFOLOGIS DAN PERUBAHAN SEMANTIK - Kusumawati, Anggara Jatu (Adabiyyāt: Jurnal Bahasa dan Sastra, 2018)
This study aims to investigate the formation process slang of Australian English. This research employs a qualitative-descriptive approach. The data of this research are conversation transcripts of Australians consisting three males and one female and being analysed analytically to find the use of slang. Observational technique was used to gather the data. The researcher taped the conversation and transcribed them to make the data analysis easier. Slang is formed into a morphological and semantic process. The morphological processes consist of derivation, clipping, blending, acronym, and alliteration. The semantic process consists of generalization, metaphor, specialization, and arbitrary process. The use of slang affects the society in terms of social and communication function. Knowing this intensely helps non natives to get close and increase more understanding in communicating with Australians.